Cooking Class Nastar Premium Dan Nasi Arab Sebagai Sarana Pemberdayaan Kelompok Perempuan Alumnus Pesantren - Majduddin, Mohammad; Fattah, Abdul; Sa'diyah, Fatichatus (MESTAKA: Jurnal Pengabdian Kepada Masyarakat, 2024)
Boarding school education has a positive impact on children's spiritual development and religious knowledge. However, the intensive learning process can also have a negative impact on their overall growth. The students spend most of their time in class learning religious teachings and texts, which while beneficial for knowledge, often leads to a lack of focus on important life skills. As a result, many students may not acquire basic skills such as cooking and others necessary to navigate life outside of their religious institution. In response to these issues, a community service activity focusing on cooking training for alumni of Pondok Pesantren Mamba'us Sholihin Gresik was organized. This training aims to equip the alumni with the skills to prepare typical Eid dishes. The implementation of this training includes preparation and implementation stages. Overall, the participants enjoyed the experience and expressed confidence to try the recipes at home. Feedback was mostly positive, with some participants expressing interest in selling their cakes. However, there were some challenges encountered, mainly related to the use of premium ingredients that may not be financially affordable for some participants. In addition, the limited availability of necessary cooking equipment may hinder their ability to practice independently.